Spatial dimension changes in second hand housing prices in Alcalá de Henares and León (Spain) - González González,María Jesús (2014)
The objective of this study is to show different recent trends (20012009) in second hand housing prices in Spain and in different neighbourhoods in Alcalá de Henares and León, both of which are cities with very diverse economic and demographic characteristics. The first is a city in the metropolitan area of Madrid, with high land prices. The increasing demand for housing in Alcalá de Henares is a good alternative for households, in view of high prices in Madrid. The second is Léon, the capital of the province of León, which is undergoing a depopulation process. We will demonstrate that house price dynamics is a local phenomenon and national or regional level data conceal interesting differences within cities (districts and neighbourhoods). The latest rise and decline in housing prices is clearly visible on the outskirts and sometimes non existent in the town centre area.